THE DEVELOPMENT OF INTERACTIVE QUIZ BASED ON QUIZIZZ OF RESPIRATORY SYSTEM MATERIALS TO TRAIN HOTS OF GRADE XI OF SENIOR HIGH SCHOOL - Dyah Ayu Ning Tyas; Nur Qomariyah (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2023)
Higher-order thinking skills (HOTS) are one of the skills that demanded in the 21st century. However, there are still few students who master this skill. The use of technology should be optimized even more in distance learning to support the learning process to achieve maximum results. Therefore, an effort is needed to train students' HOTS. One way to train HOTS is by giving quizzes in the evaluation process by utilizing the Quizizz application. This research aimed to create an interactive quiz based on Quizizz to train HOTS on respiratory system materials that are valid and reliable. This development research referred to the ASSURE model (Analyze Learner, State Objective, Select Media and Materials, Utilize Media and Materials, Require Learner Participation, Evaluate and Revise). The limited trial was conducted on 18 students of class XI MIA 2 SMA Muhammadiyah 10 GKB Gresik. The validity of the interactive quiz was determined based on the results of the validation by material expert and media expert using the validation sheet. The results showed that the validity of the interactive quiz reached 99.73% with a very valid category. Reliability and difficulty level are determined based on the student test results. The reliability of the items scored 0.713 with a reliable category. The proportion of the item difficulty level is 80% with moderate category and 20% with difficult category. Accordingly, the interactive quiz on respiratory system materials for practicing HOTS is valid and reliable. Keywords: Interactive quiz, HOTS, Quizizz, Respiratory system